Atributos produtivos e qualitativos de grãos e fisiológicos e sanitários das sementes de cultivares de feijão - Pinto, Carolina Cipriano [UNESP] (2015)
The new cultivars of common bean, in addition to high productivity, the researchers seek to meet the demands of consumers on the quality attributes and for use as seeds they are also concerned about the physiological attributes and health. The objectives of this study were to evaluate the performance of bean cultivars of Rio's commercial group as productive and qualitative attributes of the beans, check the possibility of obtaining seeds with good physiological and sanitary quality, both in the winter-spring season, and to study the influence of storage on quality, physiological and health attributes. The experimental design was a randomized block, with four replications. The treatments were consisted for 13 common bean cultivars (Pérola, BRSMG Majestoso, BRS Estilo, BRSMG Madrepérola, IPR Campos Gerais, IPR Tangará, IPR Andorinha, IPR 139, IAC Imperador, IAC Formoso, IAC Alvorada, IAC Milênio and Bola Cheia). As for productive attributes, all cultivars have high productivity, stands out BRSMG Majestoso. As regards the qualitative attributes, all cultivars have high yield sieve protruding, highlighting the IPR Andorinha. The storage period does not significantly alter the qualitative attributes of grains, keep most of the essential features to the consumer market. The seeds have appropriate physiological quality, germination and vigor decreased after eight months of storage. As regards health attributes, the storage condition increases the development of the fungus Penicillium spp., Aspergillus spp. and Rhizopus sp. Seed production is possible at this time, with better results the IAC Imperador